Respuesta :

The translation of the points as Z' ( - 8 , - 3 ), K' ( - 7 , 0 ) and K' ( - 5 , 0 ).

We are given the translation as:

(x , y)  → (x - 5 , y + 1)

Now we have some points:

Z (−3, –4)

K (−2, −1)

M (0, -1)

We need to translate these points.

For Z (−3, –4), we get the translation as:

Z (−3, –4) = Z' ( - 3 - 5 , - 4 + 1)

Z (−3, –4) = Z' ( - 8 , - 3 )

For K (−2, −1), we get the translation as:

K (−2, −1) = K' ( - 2 - 5 , - 1 + 1)

K (−2, −1) = K' ( - 7 , 0 )

For M (0, -1), we get the translation as:

M (0, -1) = K' ( 0 - 5 , - 1 + 1)

M (0, -1) = K' ( - 5 , 0 )

Therefore, we get the translation of the points as Z' ( - 8 , - 3 ), K' ( - 7 , 0 ) and K' ( - 5 , 0 ).

Learn more about translation here:

https://brainly.com/question/25950911

#SPJ9

ACCESS MORE